The training intensity distribution among well-trained and elite endurance athletes - Stöggl, Thomas L.; Sperlich, Billy (Frontiers in Physiology, 2015)
Researchers have retrospectively analyzed the training intensity distribution (TID) of nationally and internationally competitive athletes in different endurance disciplines to determine the optimal volume and intensity for maximal adaptation. The majority of studies present a “pyramidal” TID with a high proportion of high volume, low intensity training (HVLIT). World-class athletes appear to adopt a so-called “polarized” TID (i.e. significant % of HVLIT and high-intensity training), rather than a pyramidal or “threshold” (THR) TID. In contrast to the pyramidal TID, emerging prospective randomized controlled studies have demonstrated superior responses of variables related to endurance when applying a polarized TID in well-trained and recreational individuals. The aims of the present review are to: 1) summarize the main responses of retrospective and prospective studies exploring TID; 2) provide a systematic overview on TIDs during preparation, pre-competition, and competition phases in different endurance disciplines and performance levels; 3) address whether one TID has demonstrated greater efficacy than another; and 4) highlight research gaps in an effort to direct future scientific studies.